{2-[(1,3-Benzothiazol-2-yl)methoxy]-5-chlorophenyl}(4-chlorophenyl)methanone - Venugopala, K. N. (International Union of Crystallography, 2013)
In the title compound, C21H13Cl2NO2S, the benzothiazole ring makes dihedral angles of 0.94 (1) and 70.65 (5)° with the 4-chlorophenylmethanone unit and the 5-chlorophenyl ring, respectively. The dihedral angle between the 4-chlorophenylmethanone unit and the 5-chlorophenyl ring is 66.20 (5)°. The crystal structure consists of dimeric units generated by C—H⋯N hydrogen bonds, further linked by C—H⋯O and C—H⋯π interactions, leading to a three-dimensional network.